2019
DOI: 10.5194/gmd-12-1423-2019
|View full text |Cite
|
Sign up to set email alerts
|

HOMMEXX 1.0: a performance-portable atmospheric dynamical core for the Energy Exascale Earth System Model

Abstract: Abstract. We present an architecture-portable and performant implementation of the atmospheric dynamical core (High-Order Methods Modeling Environment, HOMME) of the Energy Exascale Earth System Model (E3SM). The original Fortran implementation is highly performant and scalable on conventional architectures using the Message Passing Interface (MPI) and Open MultiProcessor (OpenMP) programming models. We rewrite the model in C++ and use the Kokkos library to express on-node parallelism in a largely architecture… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…A smaller number of nodes shows much better agreement with the ideal scaling, which highlights a loss of efficiency when running in a higher throughput regime. This is consistent with the results of (Bertagna et al, 2019) who showed that Cori-KNL efficiency can vary with the amount of workload per node.…”
Section: Model Performancesupporting
confidence: 92%
“…A smaller number of nodes shows much better agreement with the ideal scaling, which highlights a loss of efficiency when running in a higher throughput regime. This is consistent with the results of (Bertagna et al, 2019) who showed that Cori-KNL efficiency can vary with the amount of workload per node.…”
Section: Model Performancesupporting
confidence: 92%
“…See Bertagna et al. (2019) and Bertagna et al. (2020) for a description of our design strategy and initial performance results.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Our ultimate goal is to make SCREAM as fast as possible on exascale machines by writing it in C++ using the Kokkos library (Carter-Edwards et al, 2014) for performance portability. See Bertagna et al (2019) and Bertagna et al (2020) for a description of our design strategy and initial performance results. We are, however, approaching this goal by first creating a prototype version in Fortran using the existing E3SM atmosphere infrastructure.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Bertagna et al also rewrote the Fortran code of the High-Order Methods Modeling Environment (HOMME) in C++ and used the Kokkos library to express on-node parallelism. Then, HOMME achieved good performance on the GPU [32].…”
Section: Related Workmentioning
confidence: 97%